The internet of things: Insights into the building blocks, component interactions, and architecture layers - Kumar, Nallapaneni Manoj; Mallick, Pradeep Kumar (Elsevier, 2018)
This paper deals with the internet of things (IoT) which has become a promising and vibrant technology to build power full smart systems to monitor and analyze various real time operating systems. In recent years a wide range of IoT applications have been developed. To understand the IoT concept, this paper studies the insights into the four building blocks of IoT (Things, Gateways, Network infrastructure, and Cloud infrastructure), three main components of IoT (The Things with Networked Sensors and Actuators, Raw Information and Processed Data Stores, and Analytical and Computing Engines) along with architecture layers (Three Layer, Five Layer, Six Layer, Seven Layer, Cloud, and FOG). The interaction between three components of IoT is also presented. The main contribution of this paper is that it summarizes the IoT, IoT building blocks, components and their interactions along with architecture layers systematically.